Implementation Risk Control Law Number 2 of 2022 By Commission V House of Representatives of The Republic of Indonesia Period 2019 – 2024 - Rinelda Bandaso Tangketasik; Poerwaningsih S. Legowo (Publikasi Indonesia, 2024)
Controlling Risks in the Implementation of Law of the Republic of Indonesia No. 2/2022 concerning Road by Commission V DPR RI for the 2019-2024 Period. Jakarta: Postgraduate Program at the Christian University of Indonesian Jakarta, 2022. This research is aiming to analyze the control of the implementation of Law RI No. 2/2022 about Road based on revision result of UU RI No. 38/2004. The qualitative method is used this research and had designed 2 main constructs, namely risk control which refers to the Bow Tie Analysis (BTA) paradigm that recommended by ISO 31000: 2008 and George Edwards' implementation paradigm which has 4 variables as following Communication, Resources, Attitudes, and Bureaucratic Structure. The research objects are members of Commission V DPR RI for the 2019-2024 period in carrying out supervisory/control functions. The results of this research indicate that implementation risks include communication distortions that use sharing information meetings (RDP) as transmission. The risk of resource variables is the occurrence of imbalances in human resources, finance/systems, processes and methods. Meanwhile, the most significant risk is the bureaucratic structure variable, the occurrence of slowness and confusion due to Standard Operational Procedures (SOP) and fragmentation of authority between institutions and ministries regarding the acceleration of increasing regional road connectivity as mandated in Presidential Instruction No. 3/2023.